Essential problems in sustainable development of ethnic minority in Vietnam - Do Van Trai; Pham Hong Trang; Nguyen Thi Thu Trang (Social Work & Society, 2020)
Vietnam's achievement in economic growth and poverty reduction over the past two decades has been remarkable: The proportion of poor people spending has decreased from 58% in the early 1990s to 14% in 2008 and 20.7% in 2012. However, ethnic minority groups account for a very high proportion of the total number of poor people and suffer from many deprivations in Vietnam. Although ethnic minority groups only account for nearly 15% of the total population of the country, they account for 47% of the poor and account for 68% of the extreme poor, according to 2010 statistics - and the gap between ethnic groups and Kinh ethnic continue to increase. The task of comprehensive poverty reduction and growth will not be possible if the ethnic minority poverty issues are not properly concerned or sustained. The Ethnic Minority Working Group (EMWG) is a network of development agencies and research specialists working on ethnic minority (EM) issues in Vietnam. Based on the experience of group members' program implementation, this paper presents five (05) issues identified by the EMWG as extremely important for the sustainable development of ethnic minorities in Vietnam.